Demographic Change and Social Welfare Times - Hasan Ali Milad Faraj (Journal of Scientific and Human Dimensions, 2026)
This study aims to examine the impact of demographic changes on social welfare systems, focusing on the population transformations occurring in modern societies, including declining fertility rates, increased life expectancy and population aging, as well as internal and external migration and rapid urbanization. The study also explores the concept of social welfare, its objectives, and the historical development of social welfare systems—from traditional charitable care to the modern welfare state culminating in the contemporary challenges these systems face.The study highlights the challenges posed by demographic changes, such as increased financial and administrative burdens on social security systems, higher demand for health and social services, and the need to redistribute resources to match population shifts. The findings emphasize that the efficiency of social welfare systems heavily depends on the adaptability of social policies and the development of long-term social protection programs to ensure social justice and improve living standards.The research concludes that understanding the relationship between demographic change and social welfare systems is essential for effective social and economic planning, ensuring sustainable social development and balancing population needs with available resources.
Keywords: Demographic Change; Social Welfare; Population Aging; Migration and Urbanization